Faith-Based Responses to the Persistence of Almajiri Education in Northern Nigeria through the Role of Islamic Organizations in Child Welfare Advocacy - Favour Uroko; Emeka Simon Ejim (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2026)
This study examines reasons for the persistence of Almajiri education in northern Nigeria. The Almajiri system faces challenges such as inadequate educational standards, limited socio-economic opportunities for participants, and cultural resistance to reforms. Despite these issues and various strategies taken to reform the Almajiri system of education, the issue has persisted. Existing literature has not adequately looked into these reasons or faith-based organisations such as the Nigerian Supreme Council for Islamic Affairs and Jama'atu Nasril Islam. The qualitative design was used with data obtained from relevant academic literature and analysed using content analysis. Findings show that the reasons for the persistence of the Almajiri system of education include a quest for survival, deep religious and cultural roots, lack of political will, resistance from Islamic religious leaders, and migration. As part of the recommendation, faith-based leaders can make it clear that street begging by children is not a requirement of Islamic education. By providing authoritative teachings, they can distinguish between authentic Qur’anic learning and harmful social practices that have evolved over time.